2019
DOI: 10.1021/acs.organomet.8b00922
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Investigation of Alkene Hydrogenation by a Pincer-Type [P2Si]Rh Complex: Alkane Release via Competitive σ-Bond Metathesis and Reductive Elimination

Abstract: A combined experimental and computational approach has been utilized to elucidate the mechanism of alkene hydrogenation by pincer-type [P 2 Si]Rh catalysts. Although [P 2 Si]Rh interacts with H 2 to afford a dihydrogen σ-complex rather than a dihydride (seemingly an indication of facile reductive elimination from Rh(III)), alkane release occurs by competitive σ-bond metathesis (bimolecular) and reductive elimination (unimolecular) pathways. This unusual behavior is attributed to the strong trans influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…It should be noted that the dihydride Rh III -complex bears a P-Rh-P bite angle of 171.7 • and does not contain a hydride trans to a phosphorus atom, that features in the way of its further reaction with the substrate (Figure2). So far as we know, a similar pattern of trans-chelating occurs mostly in pincer-metal complexes and has seldom been reported in bidentate bisphosphine-metal complexes[62].Due to the configuration of the dihydride SKP-Rh-HH with extremely crowded space around Rh, the calculation also does not show coordination of the substrate's double bond to Rh in the SKP-Rh-HH-Sub complexes. The coordination is strongly endergonic and the complex is maintained by weak intramolecular interactions.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…It should be noted that the dihydride Rh III -complex bears a P-Rh-P bite angle of 171.7 • and does not contain a hydride trans to a phosphorus atom, that features in the way of its further reaction with the substrate (Figure2). So far as we know, a similar pattern of trans-chelating occurs mostly in pincer-metal complexes and has seldom been reported in bidentate bisphosphine-metal complexes[62].Due to the configuration of the dihydride SKP-Rh-HH with extremely crowded space around Rh, the calculation also does not show coordination of the substrate's double bond to Rh in the SKP-Rh-HH-Sub complexes. The coordination is strongly endergonic and the complex is maintained by weak intramolecular interactions.…”
supporting
confidence: 53%
“…It should be noted that the dihydride Rh III ‐complex bears a P‐Rh‐P bite angle of 171.7° and does not contain a hydride trans to a phosphorus atom, that features in the way of its further reaction with the substrate (Figure 2). So far as we know, a similar pattern of trans ‐chelating occurs mostly in pincer‐metal complexes and has seldom been reported in bidentate bisphosphine‐metal complexes [62].…”
Section: Resultsmentioning
confidence: 76%
“…So far as we know, a similar form of coordination occurs only in pincer-metal complexes, and has not been reported in bidentate bisphosphinemetal complexes. [18] Due to the configuration of the dihydride SKP-Rh-HH with extremely crowded space around Rh, the calculation also does not show coordination of the substrate's double bond to Rh in theSKP-Rh-HH-Sub complexes. The coordination is strongly endergonic and the complex is maintained by weak intramolecular interactions.…”
Section: Resultsmentioning
confidence: 89%
“…In comparison to the isoelectronic P-donor sites, the silyl anion sites possess a stronger trans effect and create electron-rich metal centers that are amenable to application in catalysis. , In seminal work, Stobart et al used bis­(phosphinoalkyl)­silanes, such as [R 2 P­(CH 2 ) n ] 2 SiMeH ( I , n = 2, 3), as precursors for the preparation of pincer complexes between the related ligand I′ and metals, such as Pt, Ir, and Ru (Scheme ). It was later shown that these ethylene- and propylene-bridged ligands I′ are rather flexible, rendering the metal complexes kinetically labile, which tentatively precluded any applications in catalysis. , Thus, the more rigid bis­( o -phosphinophenyl)­silanes [R 2 P­( o -C 6 H 4 )] 2 SiMeH ( II ) have been frequently used in reactions with metals, such Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, and Au, which in most cases (except Cu, Au) provided stable pincer complexes with the related ligand II′ . The ethylene-bridged pincer ligands I′ ( n = 2) and II′ are expected to create bonding situations with similar P–M–P bite angles due to the same number of bridging carbon atoms. Many of these pincer complexes were formed via oxidative addition across the Si–H bonds and feature activated M–H bonds and have found diverse applications in catalysis, including for instance the reduction of carbon dioxide or transfer hydrogenation reactions. …”
Section: Introductionmentioning
confidence: 99%
“… It was later shown that these ethylene- and propylene-bridged ligands I′ are rather flexible, rendering the metal complexes kinetically labile, which tentatively precluded any applications in catalysis. , Thus, the more rigid bis­( o -phosphinophenyl)­silanes [R 2 P­( o -C 6 H 4 )] 2 SiMeH ( II ) have been frequently used in reactions with metals, such Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, and Au, which in most cases (except Cu, Au) provided stable pincer complexes with the related ligand II′ . The ethylene-bridged pincer ligands I′ ( n = 2) and II′ are expected to create bonding situations with similar P–M–P bite angles due to the same number of bridging carbon atoms. Many of these pincer complexes were formed via oxidative addition across the Si–H bonds and feature activated M–H bonds and have found diverse applications in catalysis, including for instance the reduction of carbon dioxide or transfer hydrogenation reactions. For the coinage metals Cu and Au, no oxidative addition was observed. …”
Section: Introductionmentioning
confidence: 99%